Mapping mad maps and recovery tools developed by mental health service users and survivors of psychiatry: a scoping review - Hernán María Sampietro; Viviana R Carmona; J Emilio Rojo; J Gómez-Benito (BMJ Open)
Background Since 1997, several tools based on the experiences of users and survivors of psychiatry have been developed with the goal of promoting self-determination in recovery, empowerment and well-being.Objectives The aims of this study were to identify these tools and their distinctive features, and to know how they were created, implemented and evaluated.Method This work was conducted in accordance with a published Scoping Review protocol, following the Arksey and O’Malley approach and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. Five search strategies were used, including contact with user and survivor networks, academic database searching (Cochrane, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, PsycARTICLES, SCOPUS, PubMed and Web of Science), grey literature searching, Google Scholar searching and reference harvesting. We focused on tools, elaborated by users and survivors, and studies reporting the main applications of them. The searches were performed between 21 July and 22 September 2022. Two approaches were used to display the data: descriptive analysis and thematic analysis.Results Six tools and 35 studies were identified, most of them originating in the USA and UK. Thematic analysis identified six goals of the tools: improving wellness, navigating crisis, promoting recovery, promoting empowerment, facilitating mutual support and coping with oppression. Of the 35 studies identified, 34 corresponded to applications of the Wellness Recovery Action Plan (WRAP). All of them, but one, evaluated group workshops implementations. The most common objective was to evaluate symptom improvement. Only eight studies included users and survivors as part of the research team.Conclusions Only the WRAP has been widely disseminated and investigated. Despite the tools were designed to be implemented by peers, it seems they have been usually implemented without them as trainers. Even when these tools are not aimed to promote clinical recovery, in practice the most disseminated recovery tool is being used in this way.